PENGARUH KARAKTERISTIK PEKERJAAN, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA INSPEKTORAT DAERAH PROPINSI SULAWESI TENGAH - Rahmah Rahmah (Katalogis, 2016)
This study aims to determine and analyze the simultaneous and partial effect of work characteristic, environment, and discipline on employees’ performance in The Inspectorate Office of Central Sulawesi Province. The research type is causal descriptive and the data is analyzed by multiple linear regression. As many as 69 samples are selected by census sample method, where all population has a chance to be chosen as a sample. The results show that work characteristics, environment, and discipline affect employees’ performance in The Inspectorate Office of 0.569 or 56.90% and the remaining of 43.10% is affected by other variables that are not covered in this study. Multiple linear regression analysis indicates that work characteristics, environment, and disicipline silmutaneously have significant effects on employees’ performance in The Office of Inspectorate Central Sulawesi Province. It also shows that work characteristics, environment, and discipline partially have significant effects on employees’ performance in The Inspectorate Office of Central Sulawesi Province.